From Instructor to Mentor: Reframing the Roles of Medical Educators in Light of the Dreyfus Model - Omer, Wafa (Journal of Rawalpindi Medical College, 2025)
There have been significant changes to the flow of educating and learning in undergraduate medical education (UGME), but one feature has remained constant: the terminology used to describe the educators. Facilitator is perhaps the most misused and overused term throughout all years of UGME, irrespective of the learners’ level or the academic activities of the teacher. This practice flattens the learners’ complexity, and the evolution of the system needs to be considered together with the multifaceted nature of teacher roles. In 1980, the Dreyfus model of skill acquisition was proposed, outlining five stages of development: from novice to expert, which are defined by growing degrees of autonomy: Novice, Advanced beginner, Competent, Proficient, and Expert.[1] This model is increasingly gaining acceptance in medical education as a framework to better understand and optimise learner progression. [2] The cognitive and psychomotor skills exhibited by the students about the competencies set for them in UGME suggest dynamic shifts which call for equally responsive teaching approaches. Therefore, it is proposed that the roles of medical educators at different levels change gradually, and this change should be accompanied by a change in terms: Instructor (1st Year – Novice Stage) In the beginning stages, where there is little experience, students need to acquire knowledge in a very systematic way, one where rules predominate. Here, teachers act as instructors by giving direct instruction and providing the students with basic information. Their responsibility is instructional and teaching centred, with steps accompanying the novice, learners who depend on set patterns and repetition will always remain, rules and repetition. [3] Coach (2nd Year - Advanced Beginner Stage) When students are given the patterns and begin the earlier forms of clinical exposure, the controllers take charge in the form of educators. Teaching patients to define, refine, and build clinical skills as well as deepen early-stage clinical reasoning for confident judgment is the objective of coaching or guidance along with correction. [4] Facilitator (3rd Year – Competent Stage) After spending adequate time through rotations, students progress in taking responsibility with little guidance. Constructivist educators become facilitators, guiding the learners in self-directed and evaluative practices pertaining to reflection along with supporting context-based application of knowledge. [5] Supervisor (4th Year – Proficient Stage) Independent functioning plus comprehensive understanding of concepts arises at this stage of knowledge paired with expression. Instructors step in as supervisors overseeing the constructive clinical activity of the students, while offering comments and guiding their free acting in/on safe space boundaries. [6] Mentor (Final Year – Expert Stage) During the last stage of the education cycle, the students are exposed to real-life examples and a professional identity as a physician. The teachers’ role from this point will now shift to mentors to assist their students through the multifaceted professional, ethical and emotional world of medicine. Helps transition the student from ‘competent’ to ‘independent, lifelong learner and responsible clinician’ [7] That the relationship changes so that students can shift instructional strategies within competency-based medical education is strong evidence towards the claim concerning its success. Adapting the phrases is much more than a mere matter of words. It recognises the changing functions and obligations of the educators throughout the spectrum of education. It is important not just for the staff but also for the students, bringing order to the whole system while improving faculty training, assessment techniques, and structuring the curriculum. For these reasons, revising the rigid allocation of facilitator for all levels of teaching is critical, and in its place, introducing a facilitator-mentor taxonomy incorporating five levels: Instructor, Coach, Facilitator, Supervisor, Mentor. Such a change is necessary with documented pedagogical frameworks accompanying teaching for the sophisticated dynamics of teaching in contemporary medical training.